Mathematical description of the distribution logistics processes of consignment seller dietary supplement manufacturing companies - Szentesi, Szabolcs; Béla, Illés; Tamás, Péter (Journal of Production Engineering, 2021)
Consignment sales are a special case of supply chains, as the products are never the property of the seller, so the distribution logistics network and the logic of the structure of the products are radically different from those of normal supply chains. Another problem is that the products have a shelf life. The inventory mechanism (qmin; qmax) is most often used for the commissioned stocks of companies producing food supplements and when checking the central inventory, i.e. replenishment to the maximum stock level when a certain stock level is reached. There are several factors to consider when filling up commission stocks and reviewing them by period. With the mathematical correlations of these factors, it is possible to distribute the commissioned finished products optimally. The paper deals with this problem.